2023
DOI: 10.1002/slct.202300756
|View full text |Cite
|
Sign up to set email alerts
|

Nanopesticides: A Review on Current Research and Future Perspective

Krish Chunilal Paradva,
Sarita Kalla

Abstract: The survival of humans depends critically on crop production, making crop protection absolutely essential. Numerous studies have suggested that nanopesticides could soon fully replace conventional pesticides since they are far more effective than those now in use. Due to an increase in their surface‐to‐volume ratio, nanomaterials exhibit different properties from their bulk counterparts. Nanopesticides are pesticides that have been made with these nanoparticles and have a high application efficiency and signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 151 publications
(259 reference statements)
0
0
0
Order By: Relevance
“…Ideally, nanopesticides should be formulated from natural biodegradable substances that do not cause environmental damage, such as proteins, polysaccharides, phospholipids, lipids, or phytochemicals. 107 As an example, essential oil nanoemulsions have been shown to be effective at repelling an important crop pest: red flour beetle. 108 Numerous other studies have also shown that essential oil nanoemulsions are effective pesticides against various agricultural pests.…”
Section: Nutritionmentioning
confidence: 99%
“…Ideally, nanopesticides should be formulated from natural biodegradable substances that do not cause environmental damage, such as proteins, polysaccharides, phospholipids, lipids, or phytochemicals. 107 As an example, essential oil nanoemulsions have been shown to be effective at repelling an important crop pest: red flour beetle. 108 Numerous other studies have also shown that essential oil nanoemulsions are effective pesticides against various agricultural pests.…”
Section: Nutritionmentioning
confidence: 99%